2012
DOI: 10.1074/jbc.m112.359349
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Structural Analysis of the Siderophore Synthetase AsbB through Reconstitution of the Petrobactin Biosynthetic Pathway from Bacillus anthracis

Abstract: Background: asbABCDEF mediates petrobactin production and facilitates anthrax virulence. Results: Purified AsbA-E proteins reconstituted petrobactin assembly in vitro. The crystal structure and enzymatic studies of AsbB highlight its function and role in the siderophore pathway. Conclusion: AsbB characterization demonstrated reaction flexibility and substrate positions in the binding pocket. Significance: Siderophore synthetases represent promising antimicrobial targets, and characterization of these versatile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
70
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(73 citation statements)
references
References 73 publications
(114 reference statements)
2
70
1
Order By: Relevance
“…In the siderophore oriented sequences, 46% of the sequence showed similarity with the siderophore assembly subunit i.e. siderophore synthetase AsbS [26]; 27% of the sequence showed best hit classification with pyoverdine, which are generally the fluorescent siderophore produced by the members of the pseudomonaceae family like Azotobacter , Azomonas , Pseudomonas and Rhizobacter [27]; 13% were for siderophore regulating receptor system and rest 15% showed identities with the yersiniabactin (siderophore produced by the pathogenic bacteria Yersinia pestis , Yersinia pseudotuberculosis and Yersininaenterocolitica ) [28]; aerobactin (siderophore produced by E . coli ) [29]; bacillibactin (siderophore produced by the genus Bacillus ) [30]; achromobactin (siderophore produced by Pseudomonas syringe ) [31]; enterobactin and pyochelin (siderophore produced by Pseudomonas aeruginosa ) [32] respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In the siderophore oriented sequences, 46% of the sequence showed similarity with the siderophore assembly subunit i.e. siderophore synthetase AsbS [26]; 27% of the sequence showed best hit classification with pyoverdine, which are generally the fluorescent siderophore produced by the members of the pseudomonaceae family like Azotobacter , Azomonas , Pseudomonas and Rhizobacter [27]; 13% were for siderophore regulating receptor system and rest 15% showed identities with the yersiniabactin (siderophore produced by the pathogenic bacteria Yersinia pestis , Yersinia pseudotuberculosis and Yersininaenterocolitica ) [28]; aerobactin (siderophore produced by E . coli ) [29]; bacillibactin (siderophore produced by the genus Bacillus ) [30]; achromobactin (siderophore produced by Pseudomonas syringe ) [31]; enterobactin and pyochelin (siderophore produced by Pseudomonas aeruginosa ) [32] respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It is found that the function of AsbA synthase can be compensated by AsbB. The strain deletion of AsbA synthetase with the other five genes can also synthesize part of Petrobactin (Nusca et al, 2012). The asbE gene deletion cannot synthesize Petrobactin siderophore showed that asbE gene was also a key gene in the pathway of Petrobactin siderophore synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Petrobactin is the main siderophore in Bacillus anthracis. Because it is not identified by the innate immune system and it has been found that the Petrobactin is the cardinal factor in the anthrax model, most of which is the mixed type of catechol-carboxylate siderophore (Nusca et al, 2012). It appears that Bacillibactin has higher importance in Bacillus cereus on insect model experiments (Hayrapetyan et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of 4,4 0diaminodibutylamine groups rather than spermidines in rhodopetrobactins can be explained by the substrate specificity of AsbA and AsbB. Both synthetases can be active with a range of diamine substrates, producing petrobactin analogues differing only in the polyamine linker groups (Nusca et al, 2012).…”
Section: Genomics Of Rhodopetrobactin Productionmentioning
confidence: 99%